Elementary School Students' Mathematical Process Skills in Gender Perspective - Kamid, Kamid; Fajriah, Noor; Kurniawan, Dwi Agus; Widodo, Rido Ilham (Universitas Pendidikan Ganesha, 2022)
According to PISA, the literacy rate of Indonesian students is very far behind that of other countries. It makes the ability of Indonesian students to process science far behind other countries. This study aims to analyze the differences in the process skills of male and female students in public elementary schools and private madrasah Ibtidaiyah. This study uses a type of quantitative survey method. This research was conducted in two public elementary schools (SDN) and two private Ibtidaiyah schools (MIS). The population of this study amounted to 35 people per class. The instrument in this research is process skills (PS). The methods used in collecting data are surveys and questionnaires. The students' questionnaire answers on PS were analyzed using descriptive and inferential statistics. The results of the study were that there were significant differences in process skills between male and female students in private madrasah ibtidaiyah. This research will have an impact on explaining the level of difference in process skills between male and female students in public and private schools.